Crenças sobre a língua espanhola para estudantes brasileiros do ensino fundamental: características e uma proposta de encaminhamento - Raizer, Paula Barros (2013)
Taking into account the classroom context, it is necessary to know and to comprehend the previous knowledge brought by students. The beliefs concept (BARCELOS, 1995) is recurring to try to understand this context and to help teachers to deal with the diversity they can find in the classroom and, according to Almeida Filho (1993), beliefs are fundamental parts in the process of learning a language, named by him as “Operação Global de Ensino de Línguas”. Considering the Spanish Language implantation at public schools, according to the law 11.161/05, it is necessary the study about the beliefs which future learners have about Spanish language. Likewise, this study has as a first goal to identify the beliefs about Spanish language learning and teaching in a group of people who participate in a Spanish language course at a public school. This course was offered by the Programa Institucional de Bolsa de Iniciação à Docência (PIBID)/ Capes at a school in the interior of São Paulo state. Also as a goal, it is intended to verify whether beliefs changes happened during the course as well as whether the courses influenced on it. Taking into account the contextual approach of beliefs, at the beginning of the course it was applied a questionnaire in “Likert Scale” (HORWITZ, 1988). During the course, it was asked for them to write diaries and, in the end, they wrote a text, in such a way that beliefs could be mapped, as well as possible changes. The results obtained reveal beliefs that Spanish was a difficult language to be studied and it changed at the moment students got in touch with the language, what also elucidates the pronunciation appreciation to the detriment of writing and the interest of students in having Spanish as an obligatory subject. In the end, it was propounded the critical literacy view as a way of dealing with beliefs in the classroom, since critical literacy is one educational practice which focuses on the relation between language and worldview, social practices, power, identity, citizenship, intercultural relations and globalization/location aspects (MATTOS, 2011).